Using Word Walls to Improve Students’ English Vocabulary - Lila Farisa; Arifin Syamaun; Nira Erdiana (Universitas Syiah Kuala, 2019)
This thesis was conducted to focus on the using word walls to improve students’ English vocabulary by applying quantitative research with one group pre-test and post-test. This research was aimed at finding out whether or not the use of word walls can improve students’ vocabulary at SMP Negeri 1 Ingin Jaya with focus on students’ vocabulary related to nouns. The sample of this research was the first grade students in the class of VII-A. To obtain the data, vocabulary test items were used on pretest and posttest. The result of data collection in this research shows that average posttest score is higher (85.5) than the pretest score is (63,5), so the difference score both of the test is 22. Moreover, the analysis of t-test showed that or 5,900 1.729 at the level significance 0.05 with the degree of freedom (df) 19. Based on the result, it can be concluded that Ha is accepted and Ho is rejected, which means that word walls can improve students’ English vocabulary. Therefore, a words wall is recommended as a good media in teaching vocabulary.